Doctor Retention: A Cross-sectional Study of How Ireland Has Been Losing the Battle - Ruairi Brugha; Nicholas Clarke; Louise Hendrick; James Sweeney (Kerman University of Medical Sciences, 2021)
BackgroundThe failure of some high-income countries to retain their medical graduates is one driver of doctor immigration from low- and middle-income countries. Ireland, which attracts many international medical graduates, implemented a doctor retention strategy from early 2015. This study measures junior doctors' migration intentions, the reasons they leave and likelihood of them returning. The aim is to identify the characteristics and patterns of doctors who plan to emigrate to inform targeted measures to retain these doctors. MethodsA national sample of 1148 junior hospital doctors completed an online survey in early 2018, eliciting their experiences of training and working conditions. Respondents were asked to choose between the following career options: remain in Ireland, go and return, go and stay away, or quit medicine. Bivariate analyses and a two-stage multivariable analysis were used to model the factors associated with these outcomes. Results45% of respondents planned to remain in Ireland, 35% leave but return later, 17% leave and not return; and 3% to quit medicine. An intention to go abroad versus remain in Ireland was independently associated (P < .05) with the doctor being under 30 years (odds ratio [OR] = 1.09 per year under 30), a non-European Union (EU) national (OR = 1.54), a trainee (OR = 1.50), and with hospital specialization, especially in Anesthesiology (OR = 5.09). Respondents were more likely to remain if they had experienced improvements in supervision and training costs. Intention to go abroad and not return versus go and return was independently associated (P < .05) with: age over 30 years (OR = 1.16 per year over 30); being a non-EU (OR = 9.85) or non-Irish EU (OR = 3.42) national; having trained through a graduate entry pathway (OR = 2.17), specializing in Psychiatry (OR = 4.76) and reporting that mentoring had become worse (OR = 5.85). ConclusionIreland's doctor retention strategy has not addressed the root causes of poor training and working experiences in Irish hospitals. It needs a more diversified retention strategy that addresses under-staffing, facilitates circular migration by younger trainees who choose to train abroad, identifies and addresses specialty-specific factors, and builds mentoring linkages between trainees and senior specialists.